Patient safety knowledge, attitude and practice among undergraduate health science students in South West Ethiopia - Tofik Mohammed; Emebet Woldearegay; Shemsu Kedir; Kemal Ahmed; Masrie Getnet; Esayas Kebede Gudina (Frontiers Media S.A., 2023)
BackgroundPatient safety is minimizing the risk of unnecessary damage associated with healthcare to a minimum. It has been linked as a global precedence area where substantial knowledge gaps exist. Knowledge, attitude, and practice of the healthcare providers toward patient safety have a great influence on the delivery of safe patient care. Regardless of this, the issue has not been adequately addressed in Ethiopia.ObjectiveThe main aim of this study was to assess the knowledge, attitude, practice, and factors associated with patient safety practice among undergraduate health science students at Jimma University Institute of Health.MethodsAn institution-based cross-sectional study design was conducted from May to November 2021. Data were collected from 678 undergraduate health science students using a pretested, structured and self-administered questionnaire. EPI data 3.1 was used for data entry, and SPSS version 25 was used for analysis. A binary logistic regression model was utilized to identify factors associated with outcome variables. An adjusted odds ratio with a 95% confidence interval and P < 0.05 were computed to determine the level of significance.ResultsOf the total students, only 293 (43.2%) and 308 (45.4%) had good knowledge and positive attitudes toward patient safety, respectively. Moreover, only 135 (19.9%) of the students had good practices regarding patient safety. Year of study [AOR = 3.75, 95% CI: (2.3, 9.3)], duration on practical attachment [AOR = 2.6, 95% CI: (1.2, 5.9)], and knowledge about patient safety [AOR = 2.9, 95% CI: (1.9, 3.4)] were associated with better patient safety practices.ConclusionIn the current study the practice of patient safety among health science students was low and less than half of the students had good knowledge and favorable attitudes toward patient safety. Patient safety practices were influenced by the length of the clinical attachment, the study year, and the knowledge of patient safety. This calls for patient safety courses to be included in training curricula of undergraduate health sciences students.